CHD7 deficiency in "Looper", a new mouse model of CHARGE syndrome, results in ossicle malformation, otosclerosis and hearing impairment. - Jacqueline M Ogier (Public Library of Science (PLoS), 2014)
CHARGE syndrome is a rare human disorder caused by mutations in the gene encoding chromodomain helicase DNA binding protein 7 (CHD7). Characteristics of CHARGE are varied and include developmental ear and hearing anomalies. Here we report a novel mouse model of CHD7 dysfunction, termed Looper. The Looper strain harbours a nonsense mutation (c.5690C>A, p.S1897X) within the Chd7 gene. Looper mice exhibit many of the clinical features of the human syndrome, consistent with previously reported CHARGE models, including growth retardation, facial asymmetry, vestibular defects, eye anomalies, hyperactivity, ossicle malformation, hearing loss and vestibular dysfunction. Looper mice display an otosclerosis-like fusion of the stapes footplate to the cochlear oval window and blepharoconjunctivitis but not coloboma. Looper mice are hyperactive and have vestibular dysfunction but do not display motor impairment.